Implementation of integrated thematic learning of character value - Suradika; Fatma Nurmulia; Anis Fajriati (Perkumpulan Peneliti Pendidikan dan Pengembangan Anak, 2023)
The objectives of this research are: (1) to know the planning of integrated thematic learning of character values, (2) to know the implementation of integrated thematic learning of character values, and (3) to know the evaluation of integrated thematic learning of character values ​​at MI Ruhul Ulum. The research method used descriptive qualitative with location in class II A Madrasah Ibtidaiyah Ruhul Ulum Jl. Kelapa Hijau No. 100, RT. 09/RW.03, Jagakarsa, South Jakarta, DKI Jakarta. The research was conducted from February to May 2022 or even semester 2021/2022. Data obtained through observation, interviews, and documentation. The steps of the data analysis technique are data reduction, data presentation, and conclusions. The validity of the data was checked through credibility, transferability, dependability, and confirmability tests. The results of the study concluded that: (1) In planning thematic learning, the lesson plans used have shown the integration of character values ​​in thematic learning, (2) In the implementation of thematic learning, character values ​​that often appear are religious character values, discipline character, friendly/communicative character values, fond of reading, and responsibility character values. Of the 18 existing character values, not all of them have been implemented optimally, (3) In the evaluation of thematic learning, the type of assessment by the teacher refers to the assessment in the 2013 curriculum, namely the assessment of social attitudes and the assessment of knowledge and skills.